2011
DOI: 10.1371/journal.pone.0021118
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble HLA-E in Melanoma: A New Potential Immune-Related Marker in Cancer

Abstract: BackgroundTumor-derived soluble factors, including soluble HLA molecules, can contribute to cancer immune escape and therefore impact on clinical course of malignant diseases. We previously reported that melanoma cells produce, in vitro, soluble forms of the non-classical MHC class I molecule HLA-E (sHLA-E). In order to investigate sHLA-E production by various tumors and to address its potential value as a tumor-associated marker, we developed a specific ELISA for the quantification of sHLA-E in biological flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 40 publications
6
50
0
1
Order By: Relevance
“…45 The sHLA-E occurs without b 2 m. In the intact HLA-E, the presence of b 2 m may mask some of the peptide sequences of the heavy chain. When sHLA-E is devoid of b 2 m, the peptide sequences otherwise masked by b 2 m in intact HLA-E are exposed to elicit an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…45 The sHLA-E occurs without b 2 m. In the intact HLA-E, the presence of b 2 m may mask some of the peptide sequences of the heavy chain. When sHLA-E is devoid of b 2 m, the peptide sequences otherwise masked by b 2 m in intact HLA-E are exposed to elicit an immune response.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the ability of both endothelial (19) and tumor cells (20,21) to produce sHLA-E molecules, especially in proinflammatory conditions, and documented a significant increase of serum sHLA-E levels in melanoma patients, compared with healthy donors (20). Moreover, we and others (19,22) observed that naturally produced and recombinant sHLA-E monomers decrease the allogeneic and antitumor activity of NK and CD8 T cells expressing the related inhibitory NK receptor CD94/ NKG2-A.…”
mentioning
confidence: 79%
“…The human CMV-reactive CD8 ab T cell clone specific for UL40 [15][16][17][18][19][20][21][22][23] epitope (MART.22) was derived from the PBMCs of a kidney transplant patient (23). The human melanoma-reactive CD8 ab T cell clone specific for NA17-A 1-9 epitope (H2) was derived from peptide-stimulated PBMCs (21).…”
Section: T Cell Clones and Cell Linesmentioning
confidence: 99%
See 2 more Smart Citations